Assessing the viability of drone technology for e-commerce last- mile deliveries: an analysis of customer perspectives - Muenker, Theresa Marie (2023)
The integration of drone technology in logistic systems is a rapidly growing area of scientific research. This work project reports findings from expert interviews and a survey on the viability of drone technology as a method for last-mile deliveries in the e-commerce industry alongside a comprehensive review of existing academic literature in this domain. Several influencing factors were used to discuss results from customer perspective on an economical, technological, and operational dimension. Overall, the results indicate that drones are a feasible solution for last-mile e-commerce deliveries from a customer perspective.